The White Side of Migration: 'Reflections on race, citizenship and belonging in Sweden' - Catrin Lundström (Nordic Journal of Migration Research, 2017)
‘The migrant’ tends to be imagined as a non-privileged, non-white, non-western subject in search of a better future in Europe or the United States and as such is a pre-constituted subject shaped by notions of marginalization and poverty. What kinds of stories are obscured by this recurrent image of ‘the migrant’ and how do such categorizations hamper the analysis of privilege, belonging and white normativity within studies of migration? Why are some individuals not regarded as migrants despite their migrant status? Why are other individuals seen as migrants and thus denied their national belonging in spite of their formal status as national citizens? The article develops analytical tools on migration, belonging and citizenship, with particular attention to (a) 'autochthony and belonging', (b) 'race and citizenship' and (c) 'white capital'.